The state of the system : a reality check on Canada's schools - Bennett, Paul W., 1949- (McGill-Queen's University Press, 2020)
"Over the last fifty years, Canada's public schools have been absorbed into a modern education system that functions much like Max Weber's infamous iron cage. Crying out for democratic school-level reform, the system has become a centralized, bureaucratic fortress that, every year, becomes softer on standards for students, less accessible to parents, further out of touch with communities, and surprisingly unresponsive to classroom teachers. Exploring the nature of the Canadian education order in all its dimensions, The State of the System explains how public schools came to be so bureaucratic, confronts the critical issues facing kindergarten to grade 12 public schools in all ten provinces, and addresses the need for systemic reform. Going beyond a diagnosis of the stresses, strains, and ills present in the system, Paul W. Bennett proposes a bold plan to re-engineer schools on a more human scale as the first step in truly reforming public education. In place of school consolidation and managerialism, one-size-fits-all uniformity, limited school choice, and the "success-for-all" curriculum, Bennett advocates for a new set of priorities: decentralize school governance, deprogram education ministries and school districts, listen to parents and teachers, and revitalize local education democracy. Tackling the thorny issues besetting contemporary school systems in Canada, The State of the System issues a clarion call for more responsive, engaged, and accountable public schools. "--